Wide‐Scale Population Sampling Identifies Three Phylogeographic Races of Basin Wildrye and Low‐Level Genetic Admixture with Creeping Wildrye. Issue 3 (1st May 2013) - Culumber, C. Mae; Larson, Steven R.; Jones, Thomas A.; Jensen, Kevin B.
ABSTRACT: Basin wildrye [ Leymus cinereus (Scribn. & Merr.) Á. Löve] and creeping wildrye [ Leymus triticoides (Buckley) Pilg.] are outcrossing perennial grasses native to western North America. These divergent species are generally adapted to different habitats but can form fertile hybrids. Cultivars of both species are used in agriculture and conservation, but little is known about genetic diversity and gene flow among these species. Therefore, multilocus amplified fragment length polymorphism (AFLP) genotypes and chloroplast DNA sequences were evaluated from 536 L. cinereus and 43 L. triticoides plants from 224 locations of western United States and Canada. Bayesian‐cluster analysis detected three L. cinereus races corresponding to the Columbia, Rocky Mountain, and Great Basin regions. Possible admixture between species was detected in specific areas, but only 2.2% of the plants showed more than 10% introgression. The Columbia and Great Basin races were predominantly octoploid whereas most of the Rocky Mountain accessions were tetraploid. Approximately 36 and 7% of the AFLP variation was apportioned among species and races, respectively, but no discrete marker differences were detected among these groups. Although species can be distinguished using a relatively small set of AFLP markers showing divergent allele frequencies, at least 30 markers were needed to classify plants by race. Approximately 8 and 11% of the chloroplast DNA sequence variation was apportioned among species and races, but these markers were not practically useful for species or race identification.